2015
DOI: 10.1007/s00431-015-2643-0
|View full text |Cite
|
Sign up to set email alerts
|

Compliance in oxygen saturation targeting in preterm infants: a systematic review

Abstract: During oxygen therapy in preterm infants, targeting oxygen saturation is important for avoiding hypoxaemia and hyperoxaemia, but this can be very difficult and challenging for neonatal nurses. We systematically reviewed the qualitative and quantitative studies investigating the compliance in targeting oxygen saturation in preterm infants and factors that influence this compliance. We searched PubMed, Embase, Web of Science, Cochrane, CINAHL and ScienceDirect from 2000 to January 2015. Sixteen studies were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 41 publications
3
34
0
3
Order By: Relevance
“…When the higher target range and tighter alarm limits were applied to our cohort, the SpO 2 was within target range for half of the time, in line with previous studies (20)(21)(22). Factors that might have influenced compliance in oxygen saturation targeting were discussed in a review by van Zanten et al (23). Studies have shown that when nurses had more patients to care for, this resulted in patients spending less time within the target range and more time above the target range (24,25).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…When the higher target range and tighter alarm limits were applied to our cohort, the SpO 2 was within target range for half of the time, in line with previous studies (20)(21)(22). Factors that might have influenced compliance in oxygen saturation targeting were discussed in a review by van Zanten et al (23). Studies have shown that when nurses had more patients to care for, this resulted in patients spending less time within the target range and more time above the target range (24,25).…”
Section: Discussionsupporting
confidence: 82%
“…Factors that might have influenced compliance in oxygen saturation targeting were discussed in a review by van Zanten et al. . Studies have shown that when nurses had more patients to care for, this resulted in patients spending less time within the target range and more time above the target range .…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen is one of the most widely used drugs in the care of (very) preterm infants, and arterial oxygen saturation measured by pulse oximetry (SpO 2 ) is the standard, noninvasive, continuous method used to guide oxygen therapy [6, 17, 18]. However, for preterm infants requiring supplemental oxygen, the optimum range of SpO 2 to minimize organ damage, without causing hypoxic injury, remains controversial [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…There is a tension between narrower alarm limits, which increase alarm frequency, nurse fatigue and potential wider fluctuations in saturation and wider limits which may expose infants to potentially longer periods of time outside the desired range [74]. Even in the best units many babies spend much time outside the target range, more usually hyperoxic than hypoxic [75,76]. Secondary analysis of data from the COT trial oximeters showed an association of prolonged episodes of hypoxaemia (saturation <80% for >1 min) with later death or adverse neurodevelopmental outcome [77].…”
Section: Oxygen Supplementation Beyond Stabilizationmentioning
confidence: 99%